Comparing the Morningness-Eveningness Questionnaire and Munich ChronoType Questionnaire to the Dim Light Melatonin Onset - Kantermann, Thomas (J Biol Rhythms, 2015)
The dim light melatonin onset (DLMO) is the most reliable measure of central circadian timing in humans. However, it is not always possible to measure the DLMO because sample collection has to occur in the hours before usual sleep onset, it requires staff support and considerable participant effort, and it is relatively expensive. Questionnaires that ask people about the timing of their behavior, such as their sleep, may provide an easier and less expensive estimate of circadian timing. The objective of this analysis was to compare the MEQ score derived from the Morningness-Eveningness Questionnaire (MEQ) and the MSF(sc) derived from the Munich ChronoType Questionnaire (MCTQ) to the DLMO in the largest sample to date (N = 60). Our hypothesis was that MSF(sc) would correlate more highly with the DLMO than MEQ score. Our sample of 36 healthy controls and 24 patients with delayed sleep phase disorder ranged in age from 18 to 62 years. All participants slept at times of their own choosing for a week before the assessment of their DLMO. The DLMO correlated significantly with both the MEQ score (r = –0.70, p < 0.001) and MSF(sc) (r = 0.68, p < 0.001). A linear regression using MEQ, MSF(sc), and age to predict the DLMO explained 60% of the DLMO variance. The strongest predictor of the DLMO was MSF(sc) (beta = 0.51, p = 0.001), followed by MEQ (beta = –0.41, p = 0.004), and age (beta = 0.26, p = 0.013). The beta values for MSF(sc) and MEQ score were not statistically different from each other. Nonetheless, around a 4-h range in the DLMO was observed at a given MEQ score and a given MSF(sc), indicating that neither questionnaire should be exclusively used to time light or exogenous melatonin treatment, as this could result in the mistiming of these treatments relative to the DLMO, thereby potentially worsening circadian misalignment.